Correlates of Certification Application Success in British Columbia, Saskatchewan and Manitoba - Martinello, Felice (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1996)
Time series data are used to estimate the effects of labour legislation, the political regime, and economie conditions on the proportion of certification applications granted. Applications filed with the British Columbia, Saskatchewan, and Manitoba Labour Relations Boards (1951-92) are considered and analyzed separately. Changes in labour legislation haue the largest impact on certification application success in all three provinces. The political environment is estimated to be important in British Columbia, but not in Saskatchewan or Manitoba. Economic conditions affect certification success in Saskatchewan and to a lesser extent in British Columbia, but not in Manitoba. Large changes in economic conditions are estimated to have only small effects on the proportion of applications granted.